The Role of Colchicine in Pericardial Syndromes - Lazaros, George; Imazio, Massimo; Brucato, Antonio; Vlachopoulos, Charalambos; Lazarou, Emilia; Vassilopoulos, Dimitrios; Tousoulis, Dimitris (Current Pharmaceutical Design, 2018)
Background: Colchicine is an old drug originally employed for the treatment of inflammatory disorders such as acute gout and familiar Mediterranean fever. Methods: In the past few decades, colchicine has been at the forefront of the pharmacotherapy of several cardiac diseases, including acute and recurrent pericarditis, coronary artery disease, prevention of atrial fibrillation and heart failure. In this review, we have summarized the current evidence based medicine and guidelines recommendations in the specific context of pericardial syndromes. Results: Colchicine has been firstly engaged in the treatment of recurrent pericarditis of viral, idiopathic and autoimmune origin. Shortly thereafter colchicine use has been expanded to the primary prevention of recurrences in patients with a first episode of pericarditis depicting similarly good results. The acquisition of high quality scientific data in the course of time from prospective randomized placebo-controlled trials and metanalyses have established colchicine as first line treatment option in acute and recurrent pericarditis, on top of the conventional treatment. The only concerns related to the use of colchicine are the side effects (mainly gastrointestinal intolerance) which although generally not serious, may account for treatment withdrawal in some cases. Conclusion: Colchicine has been established as a first line medication in the treatment of acute (first episode) and recurrent pericarditis on top of the conventional treatment as well as for the prevention of postpericardiotomy syndrome. It depicts a good safety profile with gastrointestinal intolerance being the most common side effect.
Keywords: recurrence